RANCANG BANGUN SISTEM INFORMASI KEHADIRAN TERINTEGRASI BERBASIS WEB - Dipati, Angga; Amrizal, Amrizal (LPPM Universitas Putera Batam, 2023)
Attendance is an important factor for an institution, especially in the field of education, in order to achieve goals related to student discipline.There are many ways to improve the attendance information system to make it better, one of which is by using computer technology through a website-based integrated attendance system. At the MSI Imadun Ghoffar Batam school, currently they still use the manual method in the attendance system, namely by recording student attendance using a book. This method is less efficient because if the attendance book is lost or exposed to water, it will inconvenience the school and harm students. In addition, the risk of errors and loss of attendance data is also greater.Based on the problems above, we have created an attendance system at MSI Imadun Ghoffar that is integrated web-based. This system is used by parents and homeroom teachers respectively. The research method used in data collection is research and library methods. Software development uses the waterfall method. By using an integrated web-based attendance system, the attendance process, data search, and attendance recap calculations are made easier and also minimize loss and errors in recording attendance data.